Yetik Ozan, Hayatı ve Şiirlerinin Tematik İncelemesi - Çolak, Ahmet Savaş (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Türk Dili ve Edebiyatı Anabilim Dalı / Türk Dili ve Edebiyatı Bilim Dalı, 2014)
Dr. Turgut Günay, dilbilimci ve bir akademisyen olduğu kadar Yetik Ozan mahlasıyla başta Töre dergisi olmak üzere çeşitli yayın organlarında şiirleri yayım-lanmış bir şairdir. 1942 yılında Manisa'nın Soma ilçesinde doğmuştur. İlköğrenimini Aydın iline bağlı çeşitli ilçe ve bucaklarında, orta öğrenimini ise Rize'de tamamlamıştır. Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Türk Dili ve Edebiyatı Bölümü'nü 1966 yılında bitirmiştir. Ardından Kütahya Lise-si'nde yaklaşık bir buçuk sene edebiyat öğretmenliği görevinde bulunmuştur. 1967 yılında Erzurum Atatürk Üniversitesi'nde asistanlık sınavını kazanmıştır. Türk Dili ve Edebiyatı Bölümü asistanlığın başlamıştır. 1972 tarihinde "Rize İli ve Ağızları" adlı tez çalışmasını tamamlayıp bilim doktoru olmuştur. 1973'te tamamladığı asker-lik sonrası Hacettepe Üniversitesi Sosyal ve Beşeri Bilimler Fakültesi Türk Dili ve Edebiyat Bölümü'nde öğretim görevlisi olarak göreve başlamıştır. Bu sürede "Türki-ye Türkçesi Grameri", "Türk Dili Tarihi", "Türkçenin Yapısı", "Eski Türkçe Uygur, Göktürk, Karahanlı Lehçeleri", "Anadolu ve Rumeli Ağızları", "İslamiyet Öncesi Türk Edebiyatı", "Bugünkü Türk Lehçeleri", " Türk Halk Şiirinde Türkler ve Biçim-ler", " Türk Kültürü" derslerini vermiştir. Akademik çalışmaların yanında, TRT Halk Müziği ve Halk Oyunlar Daire-sinde mesai dışı bir görevle yönetim kurulu üyeliğinde de bulunmuştur. 1978 yılında bir otel odasında hayatına kendini asarak son vermiştir. Şairin ölümünden sonra şiir-leri Yetik Ozan isimli bir eserde toplanmıştır. Anahtar Kelimeler: Yetik Ozan, Dr. Turgut Günay

Dr. Turgut Günay is a linguist and academician as well as a poet who wrote in various media organs such as Töre Review with a pseudonym, Yetik Ozan. In 1942, he was born in Manisa in Soma town. He completed his elementary education in different towns and countries of Aydın, and his secondary education in Rize. In 1966, he graduated from Ankara University from the Faculty of Languages, History and Geography in the department of Turkish Language and Literature. Then he carried out a duty as a literature teacher in Kütahya High School for almost one and half year. In 1967, he passed an exam for the assistantship in Erzurum Atatürk University. He began his assistantship in the department of Turkish Language and Literature. In 1972, he completed his study untitled as "Rize İli ve Ağızları" [Rize Province and its Local Dialects] and with this study he took his doctorate degree. In 1973 after completing his military service, he started to work as an instructor in Hacettepe University, Faculty of Social Sciences and Humanities, in the department of Turkish Language and Literature. During this period, he gave the following lectures: "Turkey Turkish Grammar," "History of Tur-kish Language," "The Structure of Turkish Language," "Old Uyghur, Gokturk, Ka-rakhanid Turkic Dialects," "Anatolia and Rumelian Local Dialects," "Turkish Litera-ture before Islam," "Present Turkish Dialects," "Turks in Turkish Folk Poetry and the Forms of Turkish Folk Poetry," "Turkish Culture." Beside his academic studies, he took in charge in the department of TRT Folk Music and Turkish Folk Dance as a member of board after his normal office hours. In 1978, he committed suicide by hanging himself in a hotel room. After his death, his poems were collected in a work called Yetkin Ozan. Key words: Yetkin Ozan, Dr. Turgut Günay
The Life of Yetik Ozan and Analysis of His Poems
Keywords: Biyografi; Biography; Türk şiiri; TurkishPoem; Şiir; Poem